ON THE DESIGN OF BCH CODES POLYNOMIALS FOR DIGITAL TELEVISION DVB-T2 BROADCASTING SYSTEMS - Hilman Auzan Mulyono; Khoirul Anwar; Budi Prasetya (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2020)
Digital Video Broadcasting Terrestrial{Second Generation (DVB-T2) requires a high coding rate to transmit data of high-quality video. This paper evaluates Bose-Chaudhuri-Hocquenghem (BCH) codes for the DVB-T2 to measure the gain of BCH codes. This paper evaluates the BCH codes as outer coding to be combined with other different inner encoding schemes such as Low Density Parity Check (LDPC) codes and convolutional codes to measure the best suitable inner encoding scheme. This paper also studies the performances of BCH codes for DVB-T2 specified by two different standards, i.e., (a) The European Telecommunications Standards Institute (ETSI) Technical Specification (TS) 102 831 and (b) ETSI European Standard (EN) 302 755. To obtain better error correcting capability, we propose new BCH polynomials based on the general guideline from ETSI TS 102 831 for Galois Field GF(214). We perform computer simulations to evaluate bit-error-rate (BER) performances under additive white Gaussian noise (AWGN) channel and Indonesia DVB-T2 channel model. We revealed the superiority of BCH codes in high data rate transmission, which is required for DVB-T2, and found that BCH codes are better suited to the LDPC codes as inner encoding rather than to the convolutional codes. We also confirmed that BCH codes of DVB-T2 from ETSI TS 102 831 using the proposed BCH polynomials have better performances compared to the standard polynomial of ETSI EN 302 755. We are expecting that the obtained polynomials can be adopted by the BCH codes of Indonesia DVB-T2 system. These results are expected to support the Indonesian government in determining the parameters of the BCH codes of DVB-T2 for Indonesia.